Linker modification strategies to control the prostate-specific membrane antigen (PSMA)-targeting and pharmacokinetic properties of DOTA-conjugated PSMA inhibitors - Benes̆ová, Martina; Bauder-Wüst, Ulrike; Schäfer, Martin; Klika, Karel D.; Mier, Walter; Haberkorn, Uwe; Kopka, Klaus; Eder, Matthias (Journal of medicinal chemistry, 2016)
Since prostate-specific membrane antigen (PSMA) is up-regulated in nearly all stages of prostate cancer (PCa), PSMA can be considered as a viable diagnostic biomarker and treatment target in PCa. This project is focused on the development and evaluation of a series of compounds directed against PSMA. The modifications to the linker are designed to improve the binding potential and pharmacokinetics for theranostic application. In addition, the results help to further elucidate the structure-activity relationships (SAR) of the resulting PSMA inhibitors. Both in vitro and in vivo experiments of 18 synthesized PSMA inhibitor variants showed that systematic chemical modification of the linker has a significant impact on the tumor-targeting and pharmacokinetic properties. This approach can lead to an improved management of patients suffering from recurrent prostate cancer by the use of one radiolabeling precursor, which can be radiolabeled either with 68Ga for diagnosis or with 177Lu or 225Ac for therapy.
Gesehen am 21.02.2020